Influence of Heat Processing on DNA Degradation and PCR-Based Detection of Wild-Type and Transgenic Maize. (4th July 2019) - Bitskinashvili, Kakha; Gabriadze, Inga; Kutateladze, Tamara; Vishnepolsky, Boris; Mikeladze, David; Datukishvili, Nelly
Abstract : Reliable detection of genetically modified (GM) maize is significant for food authenticity, labelling, quality, and safety assessment. This study aims to evaluate the factors influencing degradation and polymerase chain reaction (PCR) amplification of DNA from the wild type and transgenic maize (events Bt-176 and MON810) during thermal treatment at 100°C and 121°C. A new PCR method was developed targeting the Cry1Ab gene to detect insect-resistant GM plants. The yield of genomic DNAs extracted by the DNeasy plant mini kit dramatically decreased while DNAs obtained by cetyltrimethyl ammonium bromide- (CTAB-) based method did not show any visible changes in the yield by the time of processing. Treatment at 100°C did not significantly affect either genomic DNAs or amplicons. Heating at 121°C induced time-dependent degradation of genomic DNAs and exogenous Cry1Ab gene; however, it did not have any considerable influence on the exogenous 141 bp amplicons or endogenous amplicons in the range of 102 bp to 226 bp with the exception of the event MON810 extracted by the DNeasy plant mini kit. More yield was observed at 226 bp than 140 bp fragment of the invertase gene. The 141 bp fragment of the transgenic CaMV 35S promoter exhibited the highest thermal stability of all the examined amplicons. Analysis of foodstuffs demonstrated 102 bp amplicons specific for the zein gene as the effective marker to detect maize in the processed foods. The obtained results demonstrate that PCR-based detection of the wild type and transgenic maize is dependent on the combination of different parameters of crucial factors such as temperature and duration of exposure, transgenic event, DNA extraction method, DNA marker, and size and location of amplicons.